2016
DOI: 10.1177/0021998316676325
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment and venting of bubbles during vacuum bag prepreg processing

Abstract: During composites manufacturing with partially pre-impregnated fibers (i.e. “prepregs”) in Out-of-Autoclave processes, non-impregnated fabric cross-sections serve as air pathways to evacuate entrapped bubbles of air, moisture, or volatiles. The bubbles trapped within a laminate during processing lead to decreased structural performance. In this work, the motion of resin and bubbles during the processing of a characteristic prepreg is directly visualized in situ. This is performed utilizing a previously develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Voids within composite materials reduce mechanical performance, generating stress concentrations that lead to premature failure. Consequently, parts with porosity levels >1% are generally rejected [2]. Autoclaves apply pressure (and temperature) on the laminates during cure that suppress volatile evolution from the resin [3].…”
Section: Introductionmentioning
confidence: 99%
“…Voids within composite materials reduce mechanical performance, generating stress concentrations that lead to premature failure. Consequently, parts with porosity levels >1% are generally rejected [2]. Autoclaves apply pressure (and temperature) on the laminates during cure that suppress volatile evolution from the resin [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the specimens were cut out from laminates produced for actual industrial applications. Gangloff et al (2017) showed that imperfections related to air inclusion mainly originate in prepreg production, while the curing process inside the vacuum bag has a scarce influence on the overall quality.…”
Section: Current Technological Practice: Manufacturing Methodsmentioning
confidence: 99%
“…Therefore, the cladding time Δt a required for resin in the coverage layer to completely clad the mesopore of the present layer is given by Equation 12: According to the position of the coverage layer, the cladding time can be divided into the upper layer cladding time Δt au and the lower layer cladding time Δt al .The total cladding time Δt l can be obtained by Equation 13: 13To accomplish the formation of a meso-scale-void, the in-plane air entrapment and mesopore cladding by resin in the adjacent layers need to be completed firstly. If Δt t > Δt l , the mesopore has been entirely cladded when the in-plane air entrapment, so the trapped air will not change and the meso-scale-void is fully formed, its length can be obtained from Equation (9). If Δt t < Δt l , the mesopore has not been entirely cladded when the in-plane air entrapment occurs, the entrapped air can escape along the thickness direction until the mesopore is fully cladded, the final size of the meso-scale-void can be computed from Equation 14: (14) In conclusion, the length of the meso-scale-void can be obtained from the Equation 15: 153.3.…”
Section: Formation Of Meso-scale-voidmentioning
confidence: 99%
“…Once voids are formed during mold filling, it is difficult to eliminate them completely [9,10]. So studying the effects of preform structure and mold-filling parameters on void formation, and optimizing the process parameters to avoid or decrease the void formation become a significant method to improve the part quality.…”
Section: Introductionmentioning
confidence: 99%